Studies on the ecology and distribution of phytoplankton biomass in Kadalur coastal zone Tamil nadu, India - Enbarasan1, Prabhahar.C1, Saleshrani.K2; R. (Current Botany, 2011)
The present investigation is an attempt to ascertain the nature of the environment at Kadalur, a coastal village of Tamil Nadu. Pytoplankton of the palk Bay was studied during June 2009 to July 2010. For the present study three sampling Stations were fixed viz., Station 1 (Palar river), Station 2 (Palar estuary) and Station 3 (Kadalur sea coast). The percentage contribution of each group of phytoplankton was in the decreasing order of Myxophyceae > Chlorophyceae > Bacillariophyceae > Eugleninae at Station 1 and Diatoms > Dianoflagellates > Bluegreens > Greens > Others at Stations 2 and 3. However, Station 2 recorded more percentage of diatoms and dinoflagellates than Station 1 and 3. Phytoplankton population density and species diversity were high during the summer season. Phytoplankton species were invariably sparse during the monsoon season at all the stations. The density of phytoplankton population, as observed in the present study, was more or less equal with compared to the densities reported by earlier workers from various other marine environs of the South East Coast of India. It showed an inverse relationship with the nutrients concentrations. Species richness and evenness of phytoplankton showed an inverse relationship with the dominance index and the dominance index showed significant spatial variation. Distribution of chlorophyll Ã¢â‚¬ËœaÃ¢â‚¬â„¢ concentration closely followed the pattern of the fluctuation in phytoplankton population and it also varied seasonally. Phytoplankton chlorophyll Ã¢â‚¬ËœaÃ¢â‚¬â„¢ concentration increased with increasing phytoplankton standing crop and gross primary productivity. In general, Station 2 recorded more species composition, population density, gross primary productivity, and chlorophyll Ã¢â‚¬ËœaÃ¢â‚¬â„¢ concentration than Stations 1 and 3, which may be due to the occurrence autochthonous particulate food matter in freshwater. The diversity of coastal marine species may have been associated with the allochthonous species from the estuary.<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">